2023
DOI: 10.3390/biom13081184
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Insights into Liver X Receptor α in the Tumorigenesis and Therapeutics of Human Cancers

Ning Han,
Man Yuan,
Libo Yan
et al.

Abstract: Liver X receptor α (LXRα), a member of the nuclear receptor superfamily, is identified as a protein activated by ligands that interacts with the promoters of specific genes. It regulates cholesterol, bile acid, and lipid metabolism in normal physiological processes, and it participates in the development of some related diseases. However, many studies have demonstrated that LXRα is also involved in regulating numerous human malignancies. Aberrant LXRα expression is emerging as a fundamental and pivotal factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The Tumor Immune Estimation Resource (TIMER) database is a comprehensive resource that systematically analyzes immune infiltrates in various cancer types. [ 29 ] Therefore, we used the TIMER database to examine the relationship between GDF15 and various immune cell types in liver cancer. These results demonstrate a negative correlation between GDF15 expression in HCC and the presence of CD8 + T cells, NK cells, and M1 macrophages (Figure S9A–C , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The Tumor Immune Estimation Resource (TIMER) database is a comprehensive resource that systematically analyzes immune infiltrates in various cancer types. [ 29 ] Therefore, we used the TIMER database to examine the relationship between GDF15 and various immune cell types in liver cancer. These results demonstrate a negative correlation between GDF15 expression in HCC and the presence of CD8 + T cells, NK cells, and M1 macrophages (Figure S9A–C , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the LXRβ was reported to interact with Pannexin-1 (Panx1) which usually activates the P2X7 receptors (P2X7R) and triggers cell death, that induced pyroptosis in caspase-1-dependent manner in CRC ( Derangère et al, 2014 ; Loureiro et al, 2022 ). While the LXRα expression levels were observed to be lower in CRC than the normal cells, their activation via suitable ligands triggers the caspase-mediated cell death, inhibits the cell cycle, and induces apoptosis ( Han et al, 2023 ). A recent study investigated the SR9243-loaded immunoliposomes effect on CRC and found that LXR activation was mediated by SR9243, and immunoliposomes showed cytotoxic effect specifically in CD133+ cancer stem cells, and they also suggested the dual targeting is also an alternative and potent strategy ( Dianat-Moghadam et al, 2023 ).…”
Section: Lxrs In Cancermentioning
confidence: 99%
“…And also observed to induce cell cycle arrest via targeting the ATF4/TXNIP/REDD1/mTOR axis irrespective of AMPK activation in PDAC cells ( Chen et al, 2022 ). The sterol response element binding factor-1 (SREBF1) was known to be involved in the DNA repair mechanisms in cancer cells, the activated LXRs are reported to inhibit the activity of SREBF1 via LXR-SREBF1-PNKP axis and significantly promote apoptotic mediated cell death of pancreatic cancer cells ( Yang et al, 2020 ; Han et al, 2023 ). The squalene epoxidase (SQLE) promotes pancreatic cancer progression via Src/PI3K/Akt signalling pathway, and LXR agonist was known to inhibit the Src/PI3K/Akt axis, and thus they suggested the combination of SQLE and LXR agonists could possibly shut down PDAC progression by inhibiting the high cholesterol uptake in the tumor microenvironment ( Xu et al, 2023 ).…”
Section: Lxrs In Cancermentioning
confidence: 99%
“…PPARγ inhibits apoptosis, while LXRα/β upregulates cholesterol and MDR1 for drug efflux to confer cisplatin and paclitaxel resistance in OC [166,167] . PXR and CAR activation boosts cisplatin and paclitaxel resistance and downregulation suppress MDR1/ABCB1, enhancing apoptosis [168][169][170] .…”
Section: The Role Of Nuclear Receptors In Chemoresistance In Ocmentioning
confidence: 99%